RNA template-directed RNA synthesis by T7 RNA polymerase. - Cazenave, C (1994)
In an attempt to synthesize an oligoribonucleotide by run-off transcription by bacteriophage T7 RNA polymerase, a major transcript was produced that was much longer than expected. Analysis of the reaction indicated that the product resulted from initial DNA-directed run-off transcription followed by RNA template-directed RNA synthesis. This reaction occurred because the RNA made from the DNA template displayed self-complementarity at its 3' end and therefore could form an intra- or intermolecular primed template. In reactions containing only an RNA template, the rate of incorporation of NTPs was quite comparable to DNA-dependent transcription. RNA template-directed RNA synthesis has been found to occur with a great number of oligoribonucleotides, even with primed templates that are only marginally stable. In one instance, we observed a multistep extension reaction converting the oligonucleotide into a final product longer than twice its original length. Presumably, such a process could have generated some of the RNAs found to be efficiently replicated by T7 RNA polymerase.